Do social norms trump rational choice in voluntary climate change mitigation? Multi-country evidence of social tipping points - Heinz Welsch (University of Oldenburg, Department of Economics, 2021)
The rational choice model of voluntary public good provision predicts that an individual's contribution to climate change mitigation responds negatively to larger contributions by others whereas social norm theory maintains that one's own contribution is positively related to that of others. This paper tests the competing hypotheses empirically using representative data for about 30,000 individuals from 23 European countries. The paper finds that, up to a threshold percentage of others perceived to engage in mitigation, individuals' willingness to engage in mitigation themselves is lower the more other individuals are perceived to engage in such behavior, whereas the relationship is positive when the threshold is passed. Since the actual percentage of others perceived to engage in mitigation is lower than the estimated threshold (30 to 56 percent) in a number of countries, marginal increases in the percentage of others perceived to behave in a climate-friendly way may backfire by enhancing free-rider behavior. For the social norm to take grip, policy-induced non-marginal increases of perceptions may be warranted in such cases. Given that the actual level of the relevant behavior is large relative to the perceived level, informing people about the actual level constitutes a sufficiently large change to trigger an increase in the behavior studied.
Keywords: D01; D91; H41; Q54; 330; climate change; social norm; rational choice; voluntary public good provision; social tipping point